The complete mitochondrial genome of Amphinemura bulla Shimizu, 1997 (Plecoptera: Nemouridae) from Japan - Wang, Ying (Mitochondrial DNA B Resour, 2021)
The genus Amphinemura belongs to the family Nemouridae (Plecoptera) and has 205 species in the Holarctic and Oriental Regions. We sequenced the fourth complete mitochondrial genome of A. bulla Shimizu, 1997. The mitogenome is 15,827 bp long with 37 genes plus a control region with an A + T content of 68.9%. There are 10 intergenic spacers (75 bp total) and 13 gene overlaps (43 bp total). All protein-coding genes (PCGs) use normal initiation codons, except ND1 and ND5 which begin with TTG and GTG. Two PCGs (COII and ND5) use a single T as a partial termination codon. Phylogenetic analyses showed that Nemoura and Amphinemura were sister group resulting in a paraphyletic Amphinemurinae different from the morphological classification.